Crack Initiation Characteristics of Gas-Containing Coal under Gas Pressures. (7th February 2019) - Yin, Zhiqiang; Chen, Zhiyu; Chang, Jucai; Hu, Zuxiang; Ma, Haifeng; Feng, Ruimin
Abstract : In deep coal mines, coal before the working face is subjected to coupled high mining-induced stress and gas pressure. Such condition may facilitate crack formation and propagation in the coal seam, leading to serious coal and gas disasters. In this study, the mechanical properties (i.e., uniaxial compressive strength, tensile strength, and fracture toughness) of gas-containing coal with four levels of initial gas pressure (i.e., 0.0, 0.5, 1.0, and 1.5 MPa) were investigated by uniaxial compression, Brazilian disc, and notched semicircular bending loading test. A newly developed gas-sealing device and an RMT-150 rock mechanics testing machine were used. Fracture modes under different initial gas pressures were also determined. A theoretical method of fracture mechanics was used to analyze crack initiation characteristics under gas adsorption state. Results show that the uniaxial compressive strength, tensile strength, and fracture toughness of gas-containing coal decreased with increasing initial gas pressure. The tensional fracture occurred in gas-containing coal under uniaxial compressive loading with high gas pressure. Cracks in gas-containing coal propagated under small external loads due to the increase in effective stress of crack tip and decrease in cracking strength. This study provided evidence for modifications of the support design of working face in deep coal mines. Furthermore, the correlations between fracture toughness, compressive strength, and tensile strength of gas-containing coal were investigated.